CoCl2 induced hypoxia enhances osteogenesis of rat bone marrow mesenchymal stem cells through cannabinoid receptor 2. (December 2019) - Zhang, Menghan; Shi, Xinlian; Wu, Jingxiang; Wang, Yi; Lin, Jian; Zhao, Ya; Li, Huimin; Ren, Manman; Hu, Rongdang; Liu, Fen; Deng, Hui
Highlights: CoCl2 induced osteogeneis of rBMSCs via MAPK pathways. CoCl2 increased the mRNA and protein expressions of CB2 in rBMSCs. Inhibition of CB2 attenuated CoCl2 induced osteogenesis of rBMSCs. CoCl2 -induced MAPK pathways could be inhibited by CB2 antagonizer. Abstract: Objectives: This study aims to investigate the role of Cannabinoid receptor 2 (CB2) on osteogenesis of bone marrow-derived mesenchymal stem cells (BMSCs) under hypoxia. Materials and methods: BMSCs were isolated from Sprague-Dawley rats and cultured in the presence of cobalt chloride (CoCl2 ) to induce intracellular hypoxia. Cell proliferation was measured with MTT assay. Quantitative real-time PCR and western blot were applied to evaluate the mRNA and protein expressions of CB2 and osteogenic indicators including osteocalcin, RUNX2, collagen-1 and osterix (SP7). The osteogenic differentiation of BMSCs was further examined by ALP assay and alizarin red S (ARS) staining. Moreover, the activation of MAPKs signaling pathways was analyzed by western blot. Results: CoCl2 dose-dependently increased hypoxia inducible factor while higher concentrations (200 and 400 μM) of CoCl2 markedly inhibited cell proliferation. CoCl2 induced hypoxia significantly increased the protein and mRNA expressions of osteocalcin, RUNX2, collagen-1 and osterix, along with enhanced ALP and ARS staining. Interestingly, such effects can be inhibited by the addition of CB2 inhibitor AM630. Moreover, AM630 partially inhibited hypoxia-induced p38 and ERK pathways, which may lead to a decrease in the osteogenic transcripts of RUNX2, collagen-1 and osterix. Conclusions: CoCl2 induced hypoxia could promote osteogenesis of rat BMSCs possibly through CB2.